On the optimality of joint taxation for non-cooperative couples - Volker Meier; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2010)
We present a non-cooperative model of a family's time allocation between work and a home-produced public good, and examine whether the income tax should apply to couples or individuals. While tax-induced labor supply distortions lead to overprovision of the public good, spouses' failure to internalize the collective effect of their choices points towards underprovision. A large parameter range exists for which a move from individual to joint taxation improves the welfare of both spouses. The source of Pareto-improvement consists in moving the level of the public good closer to its first-best, while an adjustment of intra-family transfers compensates the secondary earner for the increased tax load.
Keywords: D13; D62; H23; H24; J22; 330; individual taxation; joint taxation; household production; public goods; Familienbesteuerung; Einkommensteuer; Haushaltsökonomik; Arbeitsangebot; Nichtkooperatives Spiel; Optimale Besteuerung; Theorie